2005
DOI: 10.1007/s10029-004-0309-3
|View full text |Cite
|
Sign up to set email alerts
|

Transabdominal pre-peritoneal (TAPP) versus totally extraperitoneal (TEP) laparoscopic techniques for inguinal hernia repair: a systematic review

Abstract: There is insufficient data to allow conclusions to be drawn about the relative effectiveness of TEP compared with TAPP. Efforts should be made to start and complete adequately-powered randomised controlled trials (RCTs), which compare the different methods of laparoscopic repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
2
10

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(113 citation statements)
references
References 12 publications
9
92
2
10
Order By: Relevance
“…9 Though we observed longer operative times in TEP, we had no conversion to open repair. Higher conversion rate of TEP has been reported in a large systematic review by McCormack et al 5 In this study there was 1 patient who developed seroma in post-operative period in the TAPP group. Kockerling et al found significant association of seroma formation in TAPP as compared to TEP in a large series of 17,587 patients.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…9 Though we observed longer operative times in TEP, we had no conversion to open repair. Higher conversion rate of TEP has been reported in a large systematic review by McCormack et al 5 In this study there was 1 patient who developed seroma in post-operative period in the TAPP group. Kockerling et al found significant association of seroma formation in TAPP as compared to TEP in a large series of 17,587 patients.…”
Section: Discussionsupporting
confidence: 41%
“…4 TAPP has been associated with higher rates of port-site hernias and visceral injuries whilst TEP has been associated with increased conversion rates. 5 Cochrane data analyzing directly the two techniques of laparoscopic repair do not give definitive evidence in favor of either. 6 In the scarcity of literature suggesting superiority of either of the two laparoscopic hernia repair techniques, the present study was undertaken to assess the feasibility and safety of these procedures in our set up.…”
Section: Introductionmentioning
confidence: 99%
“…In a recently published randomized trial comparing the same meshes in laparascopic extra-peritoneal inguinal hernia repair (TEP) of recurrent unilateral hernias the light weight composite (VyproII ® ) mesh group had a significantly better pain score. [28]The results from a similar study conducted by Agarwal et al,[29]where placement of lightweight Polypropylene mesh was associated with significantly better pain scores, patient comfort, and sexual function.…”
Section: Discussionmentioning
confidence: 99%
“…Successful inguinal hernia treatment without mesh can be achieved using Desarda repair, as it is effective as the standard Lichtenstein procedure. 9 But for synthetic mesh repairs, many studies have noted their association with numerous complications including persistent pain, infection, adhesions, bowel erosion, shrinkage and inflammation. 10 Time taken to return to daily activities was higher may be because those patients who had mesh repair, experience more pain and for longer duration.…”
Section: Repair Techniquesmentioning
confidence: 99%